Effects of thermal-diffusion and viscous dissipation on peristaltic flow of micropolar non-Newtonian nanofluid: Application of homotopy perturbation method - Mohamed Abou-zeid (Results in Physics, 2016)
In this paper, a study of the peristaltic motion of incompressible micropolar non-Newtonian nanofluid with heat transfer in a two-dimensional asymmetric channel is investigated under long-wavelength assumption. The flow includes radiation and viscous dissipation effects as well as all micropolar fluid parameters. The fundamental equations which govern this flow have been modeled under long-wavelength assumption, and the expressions of velocity and microrotation velocity are obtained in a closed form, while the solutions of both temperature and nanoparticles phenomena are obtained using the homotopy perturbation method (HPM). Also, the skin friction, Nusselt number and Sherwood number are obtained at both lower and upper walls. The results have been discussed graphically to observe the effects the physical parameters of the problem have on the physical quantities. Keywords: Peristaltic flow, Nanofluid, Micropolar fluid, Homotopy perturbation method